Football migration in the Czech Republic: A multi-level analysis of football migration in a semi-peripheral European Nation - Crossan, W.; Riedl, J. (Soccer & Society, 2024)
Football migration, including flows and effects, is measured over the first 27 years of the independent Czech Football League. Hierarchical multi-level analysis is used to test previous sport migration effects. Particular attention is paid to the economic and sport position of both sending and receiving nations by examining results through the world-systems theory. Though the number of football migrants continues to rapidly increase, the statistical results of this study indicate that receiving football migrants into the semi-periphery nation of Czech, where football is a primary sport, may increase winning percentage in the short term, but it does not lead to increases in fan attendance or improve the nation`s FIFA rankings. Longer term deliberation needs to be taken by individual club teams, as well as national federations, in order maximize the benefits of migration flows in the future.